Lost and found: the Plecoptera types of Blanchard and Mabille, with further contributions to the stoneflies of Chile - Murányi, Dávid; Gamboa, Maribet; Vera, Alejandro (Zootaxa, 2016)
Types of five of the six Plecoptera species described by Émile Blanchard and the holotype of the single stonefly described by Jules François Mabille were discovered in the National Museum Prague, Czech Republic. The identity of P. myrmidon Mabille, 1891 and P. pictetii Blanchard, 1854 are confirmed as Potamoperla myrmidon and Pictetoperla gayi (Pictet, 1841), respectively. Perla virescentipennis Blanchard, 1851 is considered as Diamphipnopsis virescentipennis comb. n., with Diamphipnosis samali Illies, 1960 syn. n. as a junior subjective synonym, and Diamphipnoa chillanae nom. n. is proposed for D. virescentipennis sensu Illies 1960. Lectotypes are designated for three species: Nemoura rufescens Blanchard, 1851 is redescribed as Austronemoura rufescens (Blanchard, 1851) comb. n., with Perla infuscata Blanchard, 1851 syn. n. and Perla blanchardi Jakobson & Bianchi, 1905 syn. n. designated as junior subjective synonyms, whereas Perla stictica Blanchard, 1851 is treated as Neonemura stictica (Blanchard, 1851) comb. n., nomen dubium. Paralectotypes of these three species belong to further four taxa. Due to the missing syntypes, Perla lineatocollis Blanchard, 1851 is treated as a nomen dubium of uncertain suborder assignment. Specimens of the Blanchard collections that cannot regarded as types are enumerated belonging to six species. Recent collections of 15 species from Chile are also reported.